2019
DOI: 10.3390/min9080480
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Precipitation in Fractures and Nanopores within Shale Imaged Using Time-Lapse X-ray Tomography

Abstract: Barite precipitation in fractures and nanopores within a shale sample is analysed in situ, in 3D, and over time. Diffusion of barium and sulphate from opposite sides of the sample creates a supersaturated zone where barium sulphate crystals precipitate. Time-lapse synchrotron-based computed tomography was used to track the growth of precipitates over time, even within the shale’s matrix where the nanopores are much smaller than the resolution of the technique. We observed that the kinetics of precipitation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…It can also sample large volumes, and by conducting measurements in situ, artifacts arising from sample preparation are eliminated. µ-CT has been previously employed to image the precipitation of salts within porous rocks [43][44][45] and between glass beads, [46,47] in relation to weathering processes. However, our data demonstrate that when applied to crystallization within nanoporous CPG rods, images of exceptional definition are obtained, where we were even able to distinguish between polymorphs based on their differing absorption contrast.…”
Section: Discussionmentioning
confidence: 99%
“…It can also sample large volumes, and by conducting measurements in situ, artifacts arising from sample preparation are eliminated. µ-CT has been previously employed to image the precipitation of salts within porous rocks [43][44][45] and between glass beads, [46,47] in relation to weathering processes. However, our data demonstrate that when applied to crystallization within nanoporous CPG rods, images of exceptional definition are obtained, where we were even able to distinguish between polymorphs based on their differing absorption contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of crystallization within porous rocks and manmade building materials is extremely challenging due to the heterogeneous structures of these media. Further, specialist techniques such as X-ray tomography [364,[370][371][372][373][374] are required to characterize the structure of these materials and to determine the locations and structures of the growing crystals. A range of model systems with well-defined structures and which can be characterized using laboratory techniques have therefore been employed and are outlined here.…”
Section: Crystallization In Porous Mediamentioning
confidence: 99%
“…Recent neutron scattering studies have shown that a significant proportion of pore volume in natural materials can be below 20 nm, especially in fine-grained materials such as shales that are important for energy production and carbon sequestration . Barite often precipitates during hydraulic fracturing in shales with nanopore contribution of at least 50% (<20 nm, Figure ), making the nanopore effects especially relevant to barite precipitation. ,, Even sandstone that typically has a macroscopic porosity (>10 μm) can still have a significant fraction of nanopores, as shown in Figure b. Previous transmission electron microscopy and atom probe characterization of barite particles indicate that nanopores of 1–2 nm not only exist in clays, but also within barite, possibly due to incorporation of fluid inclusion during precipitation from supersaturated solutions .…”
Section: Pore-scale Reactive Transport Modelingmentioning
confidence: 99%